Pengaruh Konsentrasi Crude Enzim Bacillus subtilis IFO 13719 terhadap Kadar Gula dan Etanol Fermentasi Kulit Coffea arabica Menggunakan Zymomonas mobilis IFO 13756 - Dheti Suraningsih; Trianik Widyaningrum (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Fossil energy is part of the needs of people in any country, including Indonesia. The need for fossil energy is increasing day by day. Therefore, efforts were made to find alternative raw materials from the non-food sector for the manufacture of ethanol. Cellulose material has potential as an alternative raw material for the manufacture of ethanol. One of the wastes that can be used is Arabica coffee skin. This study aims to determine the effect of the concentration of crude cellulase enzyme on sugar and ethanol content of fermented Arabica coffee husk using Zymomonas mobilis and to determine the concentration of crude cellulase enzyme which produces the highest sugar and ethanol content of fermented Arabica coffee husk using Zymomonas mobilis. This research is an experimental study with the independent variables, namely the concentration of crude cellulase enzymes, namely 0%, 2.5%, 5%, 7.5%, 10%, 12.5%, 15%, and 17.5% (V/V), and the dependent variable is the sugar content of hydrolysis with crude cellulase enzyme and the ethanol content of fermented with Zymomonas mobilis. The results of the experimental research were analyzed using regression test, ANOVA, and Duncan's test. The addition of crude cellulase enzyme Bacillus subtilis influence the increase in sugar and bioethanol content of fermented Arabica coffee husks using Zymomonas mobilis. The highest sugar content in the P6 treatment (concentration of crude cellulase enzyme Bacillus subtilis 15%) was 0.93 g/mL. The highest levels of bioethanol in treatment P4 (crude cellulase enzyme Bacillus subtilis concentration 10%) was 4.46%.